2023
DOI: 10.1590/1806-9282.20230240
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum leptin, insulin-like growth factor-1, and insulin-like growth factor binding protein-3 levels and clinical parameters in primary fibromyalgia patients

Yıldız Atamer,
Tugba Şahbaz,
Hatice Kübra Aşık
et al.

Abstract: SUMMARY OBJECTIVE: The aim of this study was to investigate the levels of leptin, growth hormone, insulin-like growth factor-1, and insulin-like growth factor binding protein-3 and their relations with clinical parameters in patients with primary fibromyalgia and healthy controls. METHODS: Our study was performed on 30 female patients with primary fibromyalgia and 30 healthy controls. The levels of insulin-like growth factor-1 and insulin-like growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…IGF-1 was negatively correlated with age, VAS, FMIQS, BDIS, disease duration, and tender point count 1 . It was concluded that increased serum leptin and decreased IGF-1 levels may be involved in the pathogenesis of FM 1 . The study is impressive, but some points should be discussed.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…IGF-1 was negatively correlated with age, VAS, FMIQS, BDIS, disease duration, and tender point count 1 . It was concluded that increased serum leptin and decreased IGF-1 levels may be involved in the pathogenesis of FM 1 . The study is impressive, but some points should be discussed.…”
mentioning
confidence: 93%
“…Leptin levels were positively correlated with VAS score, FMIQS, BDIS, tender point count, and disease duration 1 but negatively correlated with IGF-1 1 . IGF-1 was negatively correlated with age, VAS, FMIQS, BDIS, disease duration, and tender point count 1 . It was concluded that increased serum leptin and decreased IGF-1 levels may be involved in the pathogenesis of FM 1 .…”
mentioning
confidence: 95%
See 2 more Smart Citations